2014
DOI: 10.1016/j.measurement.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Temporal 24-hour assessment of radio frequency exposure in schools and homes

Abstract:  The WiFi duty cycle (actual usage) is measured and characterized during 24 hours.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Wireless local area networks (WLAN) based on WiFi technology are gaining popularity in schools, where devices such as tablets and laptops are being introduced as educational tools. Information on RF‐EMF exposure of children in schools is sparse, with studies mostly sampling a limited number of school locations [Juhász et al, ; Markakis and Samaras, ; Vermeeren et al, ; Verloock et al, ,]. The objective of our study was to assess indoor RF‐EMF levels to which children are exposed in a large number of primary schools in Amsterdam.…”
Section: Frequency Bands Expanded Uncertainty and Results Average mentioning
confidence: 99%
“…Wireless local area networks (WLAN) based on WiFi technology are gaining popularity in schools, where devices such as tablets and laptops are being introduced as educational tools. Information on RF‐EMF exposure of children in schools is sparse, with studies mostly sampling a limited number of school locations [Juhász et al, ; Markakis and Samaras, ; Vermeeren et al, ; Verloock et al, ,]. The objective of our study was to assess indoor RF‐EMF levels to which children are exposed in a large number of primary schools in Amsterdam.…”
Section: Frequency Bands Expanded Uncertainty and Results Average mentioning
confidence: 99%
“…Published literature includes, among others, in‐situ indoor and outdoor measurements in schools and/or playgrounds with or without personal dosimeters for the evaluation of radiofrequency (RF) electromagnetic fields (EMF) and/or extremely low‐frequency (ELF) electric and magnetic fields [Juhász et al, ; Vermeeren et al, ; Verloock et al, , ; Liorni et al, ; Struchen et al, ; Gallastegi et al, ; Birks et al, ]. In Greece, a specific legislative framework for children's playgrounds was established in 2009 in order to ensure compliance with the established exposure limits to RF EMF and extremely low‐frequency (ELF) fields [International Commission on Non Ionizing Radiation Protection (ICNIRP), ].…”
mentioning
confidence: 99%
“…cordless phone system on a landline which consists of any number of handsets and base units [7] and the Wi-Fi [20].…”
Section: / 6_________________________________________________________mentioning
confidence: 99%
“…GSM-data, GPRS (General Packet Radio Service), EDGE (Enhanced Data rates for GSM Evolution), HSDPA (High-Speed Down-link Packet Access), LTE (Long Term Evolution), Bluetooth and WLAN (Wi-Fi), [18]. Unlike older wireless networking protocols, newly introduced LTE may not be yet as protuberant due to the limited number of users subscribed to this technology [20]. In Belgium Joseph et al investigated emerging technologies and found them to contribute to the total outdoor exposure only by more than 3 per cent from UMTS-HSDPA (3G) and less than 1 per cent from LTE and WiMAX as compared to 60 per cent from GSM [14].…”
Section: Introductionmentioning
confidence: 99%